Dapagliflozin in the treatment of patients with heart failure with reduced left ventricular ejection fraction – a practical approach - Nessler, Jadwiga (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Because of its frequent occurrence, poor prognosis, low quality of life of patients accompanying the disease and high costs associated with treatment heart failure is a significant health problem in modern cardiology. The treatment of patients with heart failure and reduced ejection fraction (HFrEF) is supported by large-scale randomized clinical trials (RCTs), reflected in the ESC/HFA treatment recommendations. The use of -blockers, inhibitors of the renin-angiotensin aldosterone system (RAA), including angiotensin converting enzyme ACE/ARB inhibitors, angiotensin and neprilysin receptor blockers (ARNI) and mineralocorticoid receptor antagonists (MRA) have been a solid basis for triple HFrEF therapy over the last few years, partially altering the natural history of patients with HF. Despite this, the 5-year survival rate in HF is still lower than for some types of cancer. Therefore, the search for new drugs to improve the prognosis of this disease is still ongoing. A new group of drugs – the so-called flozins, i.e. – is a great hope for a change in the natural history of heart failure. The following article presents practical aspects of using these drugs in the treatment of patients with HFrEF, taking into account both the inclusion criteria and various clinical profiles of patients.